Factors Affecting SARS-CoV-2 Vaccination Intent and Decision Making Among African American, Native American, and Hispanic Participants in a Qualitative Study. (May 2023) - Schwartz, Benjamin; Brewer, Janesse; Budigan, Haley; Bernier, Roger; Dudley, Matthew Z.; Kan, Lilly; Proveaux, Tina M.; Roberts, Robin; Tafoya, Nadine; Hamlin, Mary Davis; Moore, Lucy; Hughes, Michael; et al.
Limited studies are available on how decisions and perceptions on SARS-CoV-2 vaccination have changed since the start of vaccination availability. We performed a qualitative study to identify factors critical to SARS-CoV-2 vaccination decision making and how perspectives evolved among African American/Black, Native American, and Hispanic communities disproportionately affected by COVID-19 and social and economic disadvantage. We conducted 16 virtual meetings, with 232 participants in wave 1 meetings (December 2020) and with 206 returning participants in wave 2 meetings (January and February 2021). Wave 1 vaccine concerns in all communities included information needs, vaccine safety, and speed of vaccine development. Lack of trust in government and the pharmaceutical industry was influential, particularly among African American/Black and Native American participants. Participants showed more willingness to get vaccinated at wave 2 than at wave 1, indicating that many of their information needs had been addressed. Hesitancy remained greater among African American/Black and Native American participants than among Hispanic participants. Participants in all groups indicated that conversations tailored to their community and with those most trustworthy to them would be helpful. To overcome vaccine hesitancy, we propose a model of fully considered SARS-CoV-2 vaccine decision making, whereby public health departments supply information, align with community values and recognize lived experiences, offer support for decision making, and make vaccination easy and convenient.